Catch rope : the long arm of the cowboy - Erickson, John R., 1943- (Denton, Tex. : University of North Texas Press, 1994)
For more than a hundred years, American cowboys have made their living through the skilled use of horse and rope. Whole libraries have been devoted to the horse, but no one, until now, has written a thorough study of the origins and evolution of ranch roping--which differs from arena roping as practiced by rodeo cowboys. Author/cowboy John Erickson studies ranch roping from every angle: its origins in the Old World; old-time loops and throws; the influence of modern team roping; and the endless debate between those cowboys who rope "hard and fast" and those who "dally." Mixing scholarship with his working--cowboy's knowledge of the subject, Erickson tells stories of cowboys who could not resist fitting their loops on "things that ort not to be roped," such as elk, deer, badgers, bears, and bobcats. He tells of jackrabbit roping contests, and of cowboys who roped mice, geese, hogs, wives, or a runaway milk wagon. Anyone who has ever "built a loop" or even thought about it will find this book hard to put down.
Who were the first ropers? -- Out of Mexico : vaqueros and cowboys -- Dally or tie -- The evolution of roping technique -- Loops and throws -- Modern ranch roping -- Roping on wheat pasture -- Doctoring pinkeye -- The rope as a weapon -- Unusual targets -- Things that ort not to be roped -- The blocker loop in Mississippi -- The pasture roping contest -- The swimming heifer -- Saving cattle with the rope -- Uncommon roping problems -- Bibliography -- Index.
"The history and evolution of ranch roping"--Half title page.
Includes bibliographical references (pages 157-167) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Calf roping -- History; Trick roping; Tours d'adresse au lasso; SPORTS & RECREATION -- Rodeos; Calf roping; Trick roping; Social Sciences; Recreation & Sports; History